2019
DOI: 10.3847/1538-4357/aaf103
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Optics Survey of Stellar Variability at the Galactic Center

Abstract: We present an ≈11.5 yr adaptive optics (AO) study of stellar variability and search for eclipsing binaries in the central ∼0.4 pc (∼10″) of the Milky Way nuclear star cluster. We measure the photometry of 563 stars using the Keck II NIRC2 imager (K′-band, λ 0 = 2.124 μm). We achieve a photometric uncertainty floor of Δm K′ ∼0.03 (≈3%), comparable to the highest precision achieved in other AO studies. Approximately half of our sample (50% ± 2%) shows variability: 52%±5% of known early-type young stars and 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 84 publications
2
44
0
Order By: Relevance
“…The first one assumes that ∼ 15 % of the stars are variable following the results of Dong et al (2017) for a 2.3 × 2.3 region centred on Sagittarius A*. The second one is a more extreme case, ∼ 50 % of variable stars, based on the results obtained by Gautam et al (2019) for the innermost region of the NSC (∼0.4 pc). We assumed a mean amplitude of H = 0.25 mag for the variable stars (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first one assumes that ∼ 15 % of the stars are variable following the results of Dong et al (2017) for a 2.3 × 2.3 region centred on Sagittarius A*. The second one is a more extreme case, ∼ 50 % of variable stars, based on the results obtained by Gautam et al (2019) for the innermost region of the NSC (∼0.4 pc). We assumed a mean amplitude of H = 0.25 mag for the variable stars (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These confirmed binaries are the most direct evidence of the broader binary population expected to reside in the GC. Observational studies suggest that the OB binary fraction in the GC is comparable to that in young massive stellar clusters (e.g., Ott et al 1999;Rafelski et al 2007), and the eclipsing young OB binary fraction in the GC is consistent with the local fraction (Gautam et al 2019). Furthermore, the theoretical study Stephan et al (2016) suggests a 70% binary fraction for the nuclear cluster given a star formation episode 6 Myrs ago (e.g., Lu et al 2013).…”
Section: Introductionmentioning
confidence: 75%
“…Recent observational and theoretical studies suggest the prevalence of binaries in the GC (e.g., Ott et al 1999;Rafelski et al 2007;Stephan et al 2016Stephan et al , 2019Naoz et al 2018;Gautam et al 2019). These binaries may have a soft orbital configuration, such that their binding energy is less than the kinetic energy of the neighboring stars.…”
Section: Discussionmentioning
confidence: 99%
“…The time-dependent positional offsets (in R.A. and Decl. with respect to Sgr A*) of the four major components of IRS13E, namely, E1, E2, E3 and E4, are obtained with the same analysis as in Gautam et al (2019) and Do et al (2019b) and are shown in Figure 4. These sources, in particular E2 and E4, show a similar westward motion, as first pointed out by (Maillard et al 2004).…”
Section: Kinematic Analysismentioning
confidence: 99%
“…Detailed information about this observation can be found in Do et al (2013). For the proper motion measurements described in Section 4, we utilize time-dependent positional information derived as a byproduct of a variability analysis of NIR sources in the GC (Gautam et al 2019), based on NIRC2 Kp-band (effective wavelength 2.124 µm) imaging observations taken between June 2005 and August 2018, in a total of 37 epochs. Detailed descriptions on the reduction and analysis of the NIRC2 data can be found in Gautam et al (2019).…”
Section: Keck Observationsmentioning
confidence: 99%